2015
DOI: 10.1590/1984-6487.sess.2015.21.06.a
|View full text |Cite
|
Sign up to set email alerts
|

Actores Y Discursos Religiosos en La Esfera Pública: Los Debates en Torno a La Educación Sexual Y a La "Muerte Digna" en Argentina

Abstract: Actores y discursos religiosos en la esfera pública: los debates en torno a la educación sexual y a la "muerte digna" en Argentina

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
(5 reference statements)
0
2
0
5
Order By: Relevance
“…Its origins are also related to the civil, political, cultural, economic, women's, and health rights movements of the 1960s. These exchange forums include the participation of religious actors, along with physicians and scientists, as religions are considered to be an authoritative voice in health-related matters (5,69). From this perspective, bioethics takes a position that advocates patients' rights and focuses on finding common ground that can serve to justify shared decisions in matters of health and biomedical research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its origins are also related to the civil, political, cultural, economic, women's, and health rights movements of the 1960s. These exchange forums include the participation of religious actors, along with physicians and scientists, as religions are considered to be an authoritative voice in health-related matters (5,69). From this perspective, bioethics takes a position that advocates patients' rights and focuses on finding common ground that can serve to justify shared decisions in matters of health and biomedical research.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that address the relationship between beliefs and the end-of-life process in biomedical settings have found that religiosity is associated with the desire to receive more aggressive treatment, rather than preparing advance directives or suspending treatment (52). These research perspectives also refer to the participation of religion in cases that have caused an impact on public opinion (53,54) and the contradictions between religious beliefs and biomedical system practices, such as the rejection of blood transfusions or surgeries by Jehovah's Witnesses (55). Social studies have also focused their interest on the end-of-life process and hospital care.…”
Section: Social Studies About the End Of Lifementioning
confidence: 99%
“…La educación sexual, como lo han planteado numerosos estudios, ha atravesado la historia de América Latina (Balderston y Guy, 1998;Theumer, 2017). El debate abierto por nuevas miradas sobre el tema ha generado una enorme diversidad en el estado legislativo y las políticas públicas en el continente; y se desarrolló tanto una actualización como una ampliación de sentidos en la comprensión, así como también, el recrudecimiento de los disciplinamientos tras los giros neoliberales (Esquivel, 2013;Torres, 2014;Esquivel y Alonso, 2015;Báez, 2020;Morán Faúndes, 2015;Vaggione, 2010).…”
Section: Educar La Sexualidadunclassified
“…Na modernidade, igreja, família e escola foram enfraquecidas como instituições transmissoras do patrimônio cultural, reforçando a missão educativa da igreja que permeia a fé na cultura, promovendo valores e, sobretudo, assumindo e aprimorando a fé de maneira profunda, sólida e duradoura. (8) Dentre os adolescentes católicos, conceitos, normas e posicionamentos acerca da sexualidade, à luz da Igreja Católica, não são explícitos, o que of computing and design, 0.70. After the analysis, suggestions and readjustments were incorporated into the website, such as the reorganization of the design and the contents on adolescence, sexuality and Sexually Transmitted Infections/HIV/AIDS, in addition to the rewriting of the text on Sexually Transmitted Infections/HIV/AIDS regarding the criteria of authorship, first impression, ease of navigation and use of graphics.…”
Section: Introductionunclassified